2005
DOI: 10.1136/bmj.38497.506481.8f
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of head louse infestation with 4% dimeticone lotion: randomised controlled equivalence trial

Abstract: Objective To evaluate the efficacy and safety of 4% dimeticone lotion for treatment of head louse infestation. Design Randomised controlled equivalence trial. Setting Community, with home visits. Participants 214 young people aged 4 to 18 years and 39 adults with active head louse infestation. Interventions Two applications seven days apart of either 4.0% dimeticone lotion, applied for eight hours or overnight, or 0.5% phenothrin liquid, applied for 12 hours or overnight. Outcome measures Cure of infestation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
2
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 13 publications
9
91
2
5
Order By: Relevance
“…this may explain the 13 % of failures at d1. this study confirms the results obtained in the two other studies (randomised controlled trials) evaluating a dimethicone-based non-conventional treatment, which reported 70 % of cure (no evidence of head lice) after two overnight applications of 4 % dimethicone lotion seven days apart (Burgess et al, 2005(Burgess et al, , 2007. But, our results are less than those obtained by heukelbach et al…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…this may explain the 13 % of failures at d1. this study confirms the results obtained in the two other studies (randomised controlled trials) evaluating a dimethicone-based non-conventional treatment, which reported 70 % of cure (no evidence of head lice) after two overnight applications of 4 % dimethicone lotion seven days apart (Burgess et al, 2005(Burgess et al, , 2007. But, our results are less than those obtained by heukelbach et al…”
Section: Discussionsupporting
confidence: 90%
“…Mémoire Parasite, 2010, 17, 329-335 problems to ensure that hair and scalp had been well covered, in particular in girls or women with long and thick hair (Burgess et al, 2005). obviously, an insufficient amount of product applied is a common cause of therapeutic failure (chosidow, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, different means of treatment depend on different aspects of the biology of headlice, and in order to choose between options in an informed fashion and to operate the chosen solution effectively it may be very useful to know something of this biology. It may be useful, for example, to distinguish between systemic pesticides with neurotoxic action and silicone-based treatments that physically affect the ability of lice to acquire oxygen or excrete water, because lice are held to be less likely to become resistant to the latter (Burgess et al 2005). In timing repeat treatments with pesticide or physical removal by combing it may help to know the length of the life cycle of lice in terms of egg hatching and maturation of larvae.…”
Section: Headlice Eradication and Parentingmentioning
confidence: 99%
“…Some of them are also fully ovicidal so a single treatment would be enough to eliminate the head louse population on the head of an infected individual. A large number of clinical trials were conducted and showed that most of them are highly effective and do not cause any significant side effects [5][6][7][8][9][10] .…”
Section: öZetmentioning
confidence: 99%